Analysis Students’ Difficulties on Using English Article at 8th Grade of SMP Negeri 1 Nuhon - Karmelia Djafar, Mila; N. Sabata, Yusniati; Lakuana, Nurhaida; Hardianti, Hardianti; Rosvita, Ita (Universitas Muhammadiyah Sorong, 2024)
This study aimed to find out the types of English Article errors made by students and also to find out some factors that cause students' difficulties in using English Articles at grade 8th students of SMP Negeri 1 Nuhon. This study used a qualitative approach as a research method. The subjects of this research were 10 students who were grade 8th students from SMP Negeri 1 Nuhon. To analyze the data, the researcher conducted test documentation and interviews using the snowball sampling method. As a result of this research, the researcher found that the students made several types of mistakes such as suspicion and confusion done by 7 students, omission by 2 students, and misformation by 8 students. Factors that influence students experiencing difficulties are the lack of knowledge about English texts, grammar, nouns, and also the students' lack of frequent opening of dictionaries, prefer used Google Translate and the difference between Indonesian as the mother tongue with English. In conclusion, this study supports and enriches the theory that has been put forward.